THE INFLUENCE OF PARENTING STYLE OF EARLY CHILDHOOD COGNITIVE DEVELOPMENT IN TANJUNG MEDAN UTARA VILLAGE - Widya Masitah; Indira Debitya Pasaribu (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the effect of parenting on early childhood cognitive development in Tanjung Medan Utara Village. This type of research is quantitative with a population of early childhood in the village of Tanjug, North Medan as many as 38 children. The sampling technique uses saturated samples. Data collection using a questionnaire. Data were analyzed using SPSS software version 2.5. The results of this study indicate that parenting practices applied to children in Tanjung Medan Utara Village are authoritarian parenting 16.1%, democratic parenting 25.0% and permissive parenting 7.2%. Then there is a relationship between parenting with the child's cognitive development. as evidenced by the Asymp 0.988 whose probability rate is below 0.05. The conclusion is that there is a relationship between parenting and cognitive development of children or with democratic parenting will provide good cognitive development, while children with authoritarian parenting will provide adequate or unfavorable development, so with permissive parenting.Keywords : Parenting Style, Early Childhood, Cognitive Development